Discrimination against the sex-diverse population in the Venezuelan armed forces: A dimension within the framework of the Organic Code of Military Justice (Revista revoluciones, 2023)
Within the global sphere, different phenomena are manifested that can constitute representations of impairment for vulnerable groups. One of these vulnerable groups is the one constituted by the sex-diverse community and an example of the events mentioned is the existence of laws that promote their discrimination. With this essay, it was intended to understand the spectrum of discrimination against the sex-diverse population in the Venezuelan armed forces as a dimension within the framework of the Organic Code of Military Justice, with special reference to its article 565. In this way, it is found that the Venezuelan State does not respect its international commitments in the field of human rights by allowing the segregation of members of the armed forces according to their sexuality, and that the criminalization of their conduct in this sense and with the support of legal norms. It even represents a violation of the rights to the free development of personality and equality, among others.
Keywords: discrimination; sexual diversity; armed forces; Venezuela